Towards an Environmental Leadership Model: Integrating Simplicity, Moral Responsibility, and Nature Harmony in Baduy Leadership - Kun Wahyu Wardana; Joko Nugroho; Antoni Ludfi Arifin (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Increasingly complex environmental challenges require leadership approaches that integrate ethical, cultural, and community-based mechanisms. This study examines how traditional leadership among the Baduy community reflects environmental concern and the lessons it offers for contemporary sustainability governance. Using a qualitative systematic literature review and thematic analysis of over fifty indexed sources, the study explores customary norms, leadership roles (Puun and Jaro), ritual practices and community resource management to identify how local wisdom shapes ecological behavior. Findings show that Baduy leadership instills environmental care through everyday norms emphasizing simplicity, harmony, and moral responsibility, fostering social-ecological resilience and strong pro-environmental practices. These findings are situated within broader debates on environmental leadership, highlighting culturally rooted mechanisms rituals, social sanctions, and leader exemplary as informal governance tools that complement formal regulations, enhance legitimacy, compliance, and low-cost conservation. The study’s main contribution is empirical and conceptual evidence that customary leadership can catalyze sustainable behavior and strengthen policy effectiveness by integrating ethical management, intergenerational responsibility, and community-based enforcement into modern environmental leadership frameworks.